Structural evaluation of recycled aggregate concrete circular columns having FRP rebars and synthetic fibers. (1st January 2022) - Raza, Ali; Hechmi El Ouni, Mohamed; Ali, Liaqat; Awais, Muhammad; Ali, Babar; Ahmad, Zeeshan; Kahla, Nabil Ben
Highlights: Novel eighteen GMRC and SMRC columns were manufactured. 3D finite element modeling (FEM) of all specimens was performed. Mostly GMRC specimens failed in the upper half portion. FEM predictions were in close correlation with test results. Abstract: Large quantity of recycled aggregate concrete (RAC) obtained from concrete and demolition waste needs to be disposed of properly and sustainably. The present investigation aims to examine the axial compressive behavior of polypropylene macro synthetic fiber (PMF) reinforced RAC (MRC) columns containing glass fiber reinforced polymer (GFRP) rebars. Nine GFRP rebars reinforced columns (GMRC columns) and nine steel rebars reinforced columns (SMRC columns) with 1200 mm height and 300 mm diameter were tested under concentric and eccentric loading. The axial load-carrying capacity (LC), failure behavior, damaging modes, and compressive deformations were assessed. The results depicted that the SMRC columns had greater axial LC by 23.4% and lower ductility capacity by 16% than GMRC columns. Mostly, the failure mechanism of GMRC and SMRC columns was similar. The application of eccentricity resulted in similar declines in axial LC for both GMRC and SMRC specimens. 3D finite element modeling of GMRC specimens was performed using a modified damaging plastic model for MRC. The suggested finite element model estimated the efficiency of GMRC specimens with high accuracy for both axial LC and corresponding deformations of samples.